Design a Quad Band Monopole Antenna for RFID, WLAN and WiMAX Application - Mohd Famee, Muhammad Mustakeen; Abdullah, Samihah; Abdul Hamid, Shabinar; Mohamad Hadis, Nor Shahanim; Yusuf Fadhullah, Solahuddin (Journal of Electronic Voltage and Application, 2022)
A small, compact size antenna with multiband frequency function has become a high demand in this modern era. This demand for this multiband frequency antenna increases throughout the year due to evolution of modern technologies that in need of small devices with multi functions. In wireless communication system, a microstrip patch antenna was introduced to fulfil the requirement of the modern technologies. The antenna is built with small  sizes with the ability to operate multiband frequencies. A quad-band monopole antenna is introduced in this paper. The purpose of this project is to design an antenna that has the capability of operating four different types of frequencies which are 915 MHz for RFID application, 2.4 GHz and 5.8 GHz for WLAN and 3.5 GHz for WiMAX application. The antenna is designed and simulated by using a Computer Simulation Technology (CST) software. The results obtained from the simulation process was analysed and recorded. The antenna is designed to have eight symmetrical rectangular strip lines microstrip patch. The substrate used for this antenna is FR-4 that has the permittivity of 4.3 and the dimension of 20 mm x 28 mm x 1.6 mm. A ground plane is constructed at the back of the antenna and it is fed with 50? microstrip line. The designing process involve three stages of antenna modification which are antenna 1 (four strip lines), antenna 2 (six strip lines) and antenna 3 (eight strip lines). The antenna managed to achieve quad band frequency in the simulation and has omni-directional radiation pattern. However, two of the operating frequency are for different frequency application. The new frequency application is 1.5 GHz for Global Positioning System (GSP) and 2.9 GHz for Third Generation (3G) application. Therefore, the results proved that the antenna designed can be used for GPS and 3G application.